MANAJEMENT OF BORDERLAND AREA - Marulitua; Oktavia Marpaung; Albert Yansen (Juremi: Jurnal Riset Ekonomi, 2021)
Trade activities that occurred at the border between Bengkayang Regency and Sarawak, specifically in Siding and Jagoi Babang districts, were in fact able to encourage domestic production. This study aims to see which management is in line with related fields in Bengkang Regency, the champion of Bengkayang Regency in Indonesia with Sarikin in Sarawak, Malaysia, which until now still uses traditional Cross-border Post or still uses the old-fashioned concept. The research method is Library Research and Field Research. As for the population in this study are the Customs and Excise staff of Jagoi Babang, the Border Society of Jagoi Babang, the Trans-Border Post Guard Officer, the Jagoi Babang Entrepreneur. The border trade model is also run coordinated and integrated by BUMDes Together by synergizing the management of the potential for natural tourism, cultural tourism and culinary tourism and handicrafts (home industries) to be part of the goods offered